2017
DOI: 10.1007/s13555-017-0184-3
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Tolerability of the Moisturizers Cetaphil® and Excipial® in Atopic Dermatitis: What is the Evidence Based on Randomized Trials?

Abstract: IntroductionMoisturizers play a prominent role in the management of atopic dermatitis by improving the impaired skin barrier function and enhancing skin hydration. Their efficacy was evaluated in a recently published Cochrane Review ‘Emollients and moisturizers for eczema’.ObjectiveIn the present review, we summarize the performance and safety of Cetaphil® and Excipial® moisturizing products.MethodsThis review was carried out in compliance with standard Cochrane methodological procedures, which means independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…Moisturizers remain the cornerstone of treatment for all severities of AD to counter and control the xerosis, decrease epidermal water loss, and improve the dysfunctional epidermal barrier. 14 A Cochrane review 36 with a focus on moisturizers that contained humectants, lipids, and/or ceramides (or their precursors) 37 reported their daily use reduced the rate of flares and enhanced the efficacy of topical steroid treatment. The panel agreed with established guidelines 14-20,23 supporting the daily use of moisturizers, alone or in combination with other therapy, for all AD patients to prevent itching, reduce flare frequency, and restore the lipid balance of the skin.…”
Section: Results Of the Panel Discussion And Consensus Statementsmentioning
confidence: 99%
“…Moisturizers remain the cornerstone of treatment for all severities of AD to counter and control the xerosis, decrease epidermal water loss, and improve the dysfunctional epidermal barrier. 14 A Cochrane review 36 with a focus on moisturizers that contained humectants, lipids, and/or ceramides (or their precursors) 37 reported their daily use reduced the rate of flares and enhanced the efficacy of topical steroid treatment. The panel agreed with established guidelines 14-20,23 supporting the daily use of moisturizers, alone or in combination with other therapy, for all AD patients to prevent itching, reduce flare frequency, and restore the lipid balance of the skin.…”
Section: Results Of the Panel Discussion And Consensus Statementsmentioning
confidence: 99%
“…Reports on proprietary emollients commonly described their efficacy and adverse effects profiles in AD treatment [3,8,46,47]. Very few studies have reported on patient’s acceptability or satisfaction of the trial emollient [6,48].…”
Section: Discussionmentioning
confidence: 99%
“…A number of proprietary emollients have undergone trials with clinical data reported in PubMed-indexed journals. Most moisturizers showed some beneficial effects, but there was generally no evidence that one moisturizer is better than the other [ 3 , 60 ]. Choosing an appropriate emollient for AD patients would improve acceptability and adherence for emollient treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by van Zuuren and colleagues in 2017, the mean duration of clinical studies on emollients (n=77) was 6.7 weeks and mean age of patients 18.6 years [ 3 , 60 ]. The clinical studies ranged from comparing studied product with vehicle or no treatment.…”
Section: Review Of Studies and Patient Preferencesmentioning
confidence: 97%
See 1 more Smart Citation